The playful undead and video games : critical analyses of zombies and gameplay - Webley, Stephen J.; Zackariasson, Peter, 1972- (New York, NY : Routledge, 2020)
"This book explores the central role of the zombie in contemporary popular culture as they appear in video games. Moving beyond traditional explanations of their enduring appeal - that they embody an aesthetic that combines horror with a mindless target; that lower age ratings for zombie games widen the market; or that Artificial Intelligence routines for zombies are easier to develop - the book provides a multidisciplinary and comprehensive look at this cultural phenomenon. Drawing on detailed case studies from across the genre, contributors from a variety of backgrounds offer insights into how the study of zombies in the context of video games informs an analysis of their impact on contemporary popular culture. Issues such as gender, politics, intellectual property law, queer theory, narrative storytelling and worldbuilding, videogame techniques and technology, and man's relation to monsters are closely examined in their relation to zombie video games. Breaking new ground in the study of video games and popular culture, this volume will be of interest to researchers in a broad range of areas including media, popular culture, video games, and media psychology"--
OCLC-licensed vendor bibliographic record.
Keywords: Video games -- Psychological aspects; Video games -- Psychological aspects -- Case studies; Zombies in popular culture; Zombies in popular culture -- Case studies; Zombies in mass media; Zombies in mass media -- Case studies; SOCIAL SCIENCE -- Media Studies; GAMES -- Video & Electronic; SOCIAL SCIENCE -- Popular Culture